European association of urology risk stratification predicts outcome in patients receiving PSMA-PET-planned salvage radiotherapy for biochemical recurrence following radical prostatectomy - Scharl, Sophia Anna Katharina; Zamboglou, Constantinos; Strouthos, Iosif; Farolfi, Andrea; Serani, Francesca; Körber, Stefan A.; Debus, Jürgen; Peeken, Jan Caspar; Vogel, Marco M. E.; Kroeze, Stephanie; Guckenberger, Matthias; Krafcsik, Manuel; et al. (Radiotherapy and oncology, 2024)
Purpose - The European Association of Urology (EAU) proposed a risk stratification (high vs. low risk) for patients with biochemical recurrence (BR) following radical prostatectomy (RP). Here we investigated whether this stratification accurately predicts outcome, particularly in patients staged with PSMA-PET. - Methods - For this study, we used a retrospective database including 1222 PSMA-PET-staged prostate cancer patients who were treated with salvage radiotherapy (SRT) for BR, at 11 centers in 5 countries. Patients with lymph node metastases (pN1 or cN1) or unclear EAU risk group were excluded. The remaining cohort comprised 526 patients, including 132 low-risk and 394 high-risk patients. - Results - The median follow-up time after SRT was 31.0 months. The 3-year biochemical progression-free survival (BPFS) was 85.7 % in EAU low-risk versus 69.4 % in high-risk patients (p = 0.002). The 3-year metastasis-free survival (MFS) was 94.4 % in low-risk versus 87.6 % in high-risk patients (p = 0.005). The 3-year overall survival (OS) was 99.0 % in low-risk versus 99.6 % in high-risk patients (p = 0.925). In multivariate analysis, EAU risk group remained a statistically significant predictor of BPFS (p = 0.003, HR 2.022, 95 % CI 1.262-3.239) and MFS (p = 0.013, HR 2.986, 95 % CI 1.262-7.058). - Conclusion - Our data support the EAU risk group definition. EAU risk grouping for BCR reliably predicted outcome in patients staged lymph node-negative after RP and with PSMA-PET before SRT. To our knowledge, this is the first study validating the EAU risk grouping in patients treated with PSMA-PET-planned SRT.
Online verfügbar: 7. März 2024, Artikelversion: 14. März 2024
Gesehen am 30.01.2025